CT breast dose reduction with the use of breast positioning and organ‐based tube current modulation. Issue 2 (February 2017) - Fu, Wanyi; Tian, Xiaoyu; Sturgeon, Gregory M.; Agasthya, Greeshma; Segars, William Paul; Goodsitt, Mitchell M.; Kazerooni, Ella A.; Samei, Ehsan
Abstract : Purpose: This study aimed to investigate the breast dose reduction potential of a breast‐positioning (BP) technique for thoracic CT examinations with organ‐based tube current modulation (OTCM). Methods: This study included 13 female anthropomorphic computational phantoms (XCAT, age range: 27–65 y.o., weight range: 52–105.8 kg). Each phantom was modified to simulate three breast sizes in standard supine geometry. The modeled breasts were then morphed to emulate BP that constrained the majority of the breast tissue inside the 120° anterior tube current (mA) reduction zone. The OTCM mA value was modeled using a ray‐tracing program, which reduced the mA to 20% in the anterior region with a corresponding increase to the posterior region. The organ doses were estimated by a validated Monte Carlo program for a typical clinical CT system (SOMATOM Definition Flash, Siemens Healthcare). The simulated organ doses and organ doses normalized by CTDIvol were used to compare three CT protocols: attenuation‐based tube current modulation (ATCM), OTCM, and OTCM with BP (OTCMBP ). Results: On average, compared to ATCM, OTCM reduced breast dose by 19.3 ± 4.5%, whereas OTCMBP reduced breast dose by 38.6 ± 8.1% (an additional 23.8 ± 9.4%). The dose saving of OTCMBP was more significant for larger breasts (on average 33, 38, and 44% reduction for 0.5, 1, and 2 kg breasts, respectively). Compared to ATCM, OTCMBP also reduced thymus and heart dose by 15.1 ± 7.4% and 15.9 ± 6.2% respectively. Conclusions: In thoracic CT examinations, OTCM with a breast‐positioning technique can markedly reduce unnecessary exposure to radiosensitive organs in anterior chest wall, specifically breast tissue. The breast dose reduction is more notable for women with larger breasts.